The Problems of the Global Educational Environment and Their Solutions from the Perspective of Islamic Education - Rozi, Bahru (Al-Jadwa: Jurnal Studi Islam, 2023)
Every child born into this world is in a state of fitrah (natural purity). However, this innate purity can undergo changes due to the influence of the environment in which they live and grow. This study aims to (1) understand the extent of environmental influence on the development of students, and (2) identify Islamic solutions for addressing global educational environmental issues. The method used in this study is library research, focusing on the collection and analysis of data from various relevant literature. The findings indicate that: (1) Substantially, the environment has a significant influence on students, both directly and indirectly. The environment in question includes the family, school, and community environments. Together, these three environments shape the character, morals, and values upheld by the students. (2) Islam offers comprehensive solutions to address global educational environmental issues by promoting the creation of integrated education. This integrated education necessitates harmonious cooperation among the three educational environments: family, school, and community. By working together, these three environments can support each other in forming a generation that is not only intellectually intelligent but also morally and spiritually strong, in accordance with Islamic teachings.